2012
DOI: 10.1186/1475-2840-11-94
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telmisartan on the expression of adiponectin receptors and nicotinamide adenine dinucleotide phosphate oxidase in the heart and aorta in type 2 diabetic rats

Abstract: BackgroundDiabetic cardiovascular disease is associated with decreased adiponectin and increased oxidative stress. This study investigated the effect of telmisartan on the expression of adiponectin receptor 2 (adipoR2) and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunits in the heart and the expression of adiponectin receptor 1 (adipoR1) in aorta in type 2 diabetic rats.MethodsType 2 diabetes was induced by high-fat and high-sugar diet and intraperitoneal injection of a low dose of streptoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…b Significant as compared to HFFD (P \ 0.05; ANOVA followed by Tukey's test) of HFFD-fed mice, suggesting that NOX might play a crucial role in the involvement of ROS production and development of diabetic heart disease. Many studies reported that the use of pioglitazone and telmisartan reduced the vascular and cardiac NADPH oxidase expression in diabetic rodents [35][36][37][38]. Our study showed Fig.…”
Section: Discussionsupporting
confidence: 63%
“…b Significant as compared to HFFD (P \ 0.05; ANOVA followed by Tukey's test) of HFFD-fed mice, suggesting that NOX might play a crucial role in the involvement of ROS production and development of diabetic heart disease. Many studies reported that the use of pioglitazone and telmisartan reduced the vascular and cardiac NADPH oxidase expression in diabetic rodents [35][36][37][38]. Our study showed Fig.…”
Section: Discussionsupporting
confidence: 63%
“…It is worth noting, however, that other association-based clinical studies linked lower circulating ADN levels to cardiovascular anomalies in diabetes 50 . Therefore, further research is needed to mechanistically evaluate the role of circulating ADN levels in health and pathological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Oxidative stress has been suggested to be involved in the development and progression of diabetes-induced cardiomyopathy [10,11,13,16]. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is the main source of reactive oxygen species in the cardiovascular tissues [36].…”
Section: Discussionmentioning
confidence: 99%